Bail support schemes for adults - Hucklesby, Anthea (Researching criminal justice series., 2011)
This important book makes a valuable contribution to an under-researched area. It includes an evaluation of the Effective Bail Scheme (EBS) and discusses the potential for the wider development of bail support schemes and some of the questions and challenges posed by their use.